On the Performance on 100 Kbps Short-Range Wireless Optical Communication Using Visible Light - Soto-Gomez, J (Institute of Electrical and Electronics Engineers Inc., 2024)
On the one hand, visible light communication (VLC) based on light-emitting diode (LED) technology offers not only lighting but also communication for various applications such as short-range wireless access, the Industrial Internet of Things (IIoT), vehicular networks (VN)s, among others. On the other hand, experimentation is the final and determining phase to validate the scientific research process in any communication system. In this work, for the first time a 100 kbps short-range wireless optical communication link utilizing visible light is developed and tested in the Latin American Region. The distance and alignment limits between the LED and the PD to obtain an error-free communication link are found taking into account the guidelines of the IEEE 802.15.7-2011 standard. © 2024 IEEE.